Implementation of Problem-Based Learning to Enhance Students Critical Thinking Skills in Junior High School - Sappaile, Baso Intang; Nisak, Sayida Khoiratun; Mustofa, Mustofa; Mendrofa, Netti Kariani; Supendi, Dede (Universitas Tanjungpura, 2025)
This qualitative study explores the implementation of Problem-Based Learning (PBL) to enhance critical thinking skills among junior high school students in Indonesia. Recognizing the limitations of traditional teaching methods that emphasize memorization, this research investigates how PBL, which centers on student-driven problem-solving, impacts students